Optimized thickness of hot-mix asphalt mixture over a chemically stabilized full-depth reclamation layer - Wu, Xingdong (My University, 2024)
Full-depth reclamation (FDR) is an in-place recycling process that utilizes the entire depth of deteriorated asphalt concrete (AC) pavement to produce a uniform stabilized base course and enhance new AC overlay performance. This study was conducted to determine the optimal stabilized FDR (SFDR) mixture design and thickness of an AC overlay over an SFDR base via laboratory and accelerated pavement testing (APT). SFDR mixtures were prepared using Portland Type I/II cement, Class C fly ash, and reclaimed asphalt pavement (RAP) materials. These mixtures were evaluated by the standard Proctor, unconfined compressive strength (UCS), vacuum saturation, and linear shrinkage tests. The AASHTOWare Pavement Mechanistic-Empirical Design (PMED) software (ver. 2.5) used the UCS test results as input parameters to determine the minimum thickness of the overlaying AC layers. Four asphalt pavement test sections of the laboratory-designed SFDR mixtures and two AC overlay thicknesses (3 and 4.5 in.) were constructed at the Kansas State University (KSU) Civil Infrastructure System Laboratory (CISL) for APT tests. The test sections were instrumented to measure horizontal strain at the bottom of the AC layer, the temperature on top of the base layer, and stress on top of the subgrade. A single axle with dual tires was used to apply an 18-kip load on each test section for 500,000 repetitions. The data acquisition system intermittently recorded strain under the AC layer and stress beneath the SFDR layer. The temperature during testing was monitored. Rutting on the test sections was quantified at certain APT loading intervals. The test sections were also inspected for any signs of cracking. APT results and the PMED software (ver.2.6.2) reanalysis showed that predicted rut depths were lower than those observed in the APT test. APT testing did not show any cracking in the sections, which was in contrast with the PMED software prediction. All sections had a much lower predicted International Roughness Index (IRI) than the PMED IRI failure criterion. The APT results showed that for SFDR mixtures that met the minimum 250 psi 7-day stabilized base UCS required by the US Army Corps of Engineers, 5% cement was the most suitable stabilizer. For the SFDR mixture design, 5% cement by dry weight of FDR material would be an appropriate starting point to do an SFDR mixture design following the US Army Corp of Engineers and Portland Cement Association guidelines. Moisture susceptibility evaluation using the vacuum saturation test is highly recommended. A comparison of the AASHTOWare PMED results and 1993 AASHTO Pavement Design Guide computations showed that the latter can be applied to the SFDR flexible pavement design. Hence, this design method is recommended for the AC overlay design. The stabilized FDR base layer structural coefficients corresponding to the unconfined compressive strengths should be taken from the 1993 AASHTO Guide nomograph. Finite element models (FEM) with moving and constant loading applications were developed to simulate the APT tests. The FEM outputs were compared with the APT test results. The FEM analysis with constant loading exhibited a similar trend to the APT results in terms of AC surface rutting and horizontal strain at the bottom of the AC layer but not for the subgrade stress. The pavement test sections with the cement-stabilized FDR layer showed lower rutting than those observed in the APT results. However, these sections had higher transverse and longitudinal strains measured at the bottom of the AC layer and stress on top of the subgrade. Better constitutive models for the SFDR mixtures are needed to be developed.
Keywords: Full-depth reclamation; Reclaimed asphalt pavement; Chemical stabilizer; Accelerated pavement testing; Flexible pavement